TV9 SEBAGAI MEDIA ISLAM ASWAJA PERSPEKTIF INTITUTION - Eko Yudi Prasetyo (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2022)
This article was written to try to answer the question, how is TV9 Aswaja as an Islamic media Institution perspective? What's TV9 like? To what extent has TV9 integrated Aswaja's values into its da'wah program? How is the community's response to the TV9 da'wah program? This research is a qualitative research using the theory of Media Institutions perspective of Gill Branston and Roy Stafford on TV9 Aswaja. TV9 is a Surabaya local television with a religious concept with a polite and demeaning program offering. TV9 in general has differences with other television stations, among which TV9 does not have advertisements in its program, because it emphasizes the concept of da'wah and Islamic studies based on Ahlussunnah Wal Jama'ah. Meanwhile, other secular and local television stations are more focused on contemporary life and commerciality. TV9 puts more emphasis on corporate edification, through providing honest, reliable information to the public and promoting goodness.